Light-emitting anchor net material suitable for stress and preparation method of light-emitting anchor net material

By preparing stress luminescent anchor mesh materials that combine holmium and dysprosium modified methylamine lead-iodine bromide nanoparticles with polyimide matrix, the complex and cost problems of tunnel stress monitoring in the prior art are solved, and the high strength, toughness and simple stress monitoring effects of the material are achieved.

CN119753874AInactive Publication Date: 2025-04-04CCTEG COAL MINING RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411867648.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, tunnel stress monitoring requires additional installation of stress monitoring meters, the process is complex and costly, and there is a lack of a simple, low-cost and high-strength stress luminescent anchor material.

Method used

By dissolving olmium-containing and dysprosium-containing soluble salts in a specific mixture, and adding lead-containing compounds and methylamine solutions, olmium-containing and dysprosium- modified methylamine lead-iodine bromide nanoparticles were prepared, combined with polyimide matrix and other materials, and stress luminescent anchor mesh materials were prepared by melt spinning braiding.

Benefits of technology

The material can emit light when it is under stress, and the luminous intensity can be used to quantitatively judge the stress magnitude. The material strength and toughness have also been improved, achieving simplicity, efficiency and economicality of tunnel stress monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753874A_ABST
    Figure CN119753874A_ABST
Patent Text Reader

Abstract

The invention provides a luminescent anchor net material suitable for stress and a preparation method thereof. The preparation method comprises the following steps: firstly, preparing holmium and dysprosium modified methylamine lead iodine bromine nanoparticles; and stirring and mixing 10-15 parts by mass of the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, 100 parts by mass of a polyimide matrix, 1-2 parts by mass of a dispersion accelerator, 1-5 parts by mass of a reinforcing agent and 1-3 parts by mass of a flexibilizer, and carrying out melt spinning and weaving at 120-140 DEG C to obtain the anchor net material. The preparation method disclosed by the invention has the characteristics of simple process, low cost and easiness in popularization and application; when the anchor net material provided by the invention is deformed under the action of external force, the anchor net material can emit light, and the magnitude of stress can be quantitatively judged according to the luminous intensity of the anchor net material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of development of new anchor net materials, and in particular to a luminous anchor net material suitable for stress and a preparation method thereof. Background Art

[0002] Anchor net support technology is one of the important means of tunnel surrounding rock control. Anchor net support can balance the deformation and stress state of each part of the tunnel, give full play to the self-bearing capacity of the surrounding rock, and closely adhere to the surrounding rock to form a unified support system to jointly bear the load, thereby improving the stability of the surrounding rock. The anchor net limits the deformation of the surrounding rock, adjusts the stress distribution of the surrounding rock, and makes the surrounding rock near the inner surface of the tunnel in a three-dimensional stress state. At the same time, it is closely attached to the surrounding rock and gives resistance and shear force to the surface of the surrounding rock to prevent the deterioration of the surrounding rock strength. The anchor bay will also allow the surrounding rock to deform to a certain extent, which is convenient for exerting the self-bearing capacity of the surrounding rock, and transfers the non-anchored rock layer load between the anchor rods to the anchor rods and the stable rock layer, so that the point support of a single anchor rod is transformed into the surface support of the support system. However, the current tunnel stress monitoring requires the additional installation of stress monitoring meters, which requires responsible processes and labor costs.

[0003] Therefore, there is an urgent need to develop a new type of stress-luminescent anchor net material that is simple, low-cost, and high-strength and suitable for tunnel stress monitoring and promote its application. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. The present application proposes a luminous anchor net material suitable for stress and a preparation method thereof, the preparation method has the characteristics of simple process, low cost and easy promotion and application; when the anchor net material provided by the present application is deformed by external force, the anchor net material can emit light and the magnitude of the stress can be quantitatively judged according to the luminous intensity of the anchor net material.

[0005] According to an embodiment of the first aspect of the present application, a method for preparing a stress luminescent anchor mesh material is provided, comprising the following steps:

[0006] Dissolving a soluble salt containing holmium and dysprosium in a mixed solution A consisting of 2-acetylbenzofuran and 1-(1-benzofuran-2-yl)ethyl](methyl)amine, and then adding a lead-containing compound to the mixed solution to obtain a solution B; dropping a methylamine solution into the solution B under stirring and ultrasonic conditions to obtain holmium and dysprosium modified methylamine lead iodine bromine nanoparticles;

[0007] By weight, 10-15 parts of the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, 100 parts of the polyimide matrix, 1-2 parts of the dispersion promoter, 1-5 parts of the reinforcing agent, and 1-3 parts of the toughening agent are stirred and mixed, and melt-spun and woven at 120-140° C. to obtain the anchor net material.

[0008] In some embodiments, in parts by mass, the soluble salt containing holmium and dysprosium is 3-5 parts; the mixed solution A is 20 parts; the lead-containing compound is 5-9 parts; the methylamine solution is 10-15 parts; the soluble salt containing holmium and dysprosium includes holmium chloride, holmium iodide, dysprosium iodide and dysprosium chloride in a mass ratio of 1:1:3:1.

[0009] In some embodiments, the mass ratio of the 2-acetylbenzofuran to the 1-(1-benzofuran-2-yl)ethyl](methyl)amine in the mixed solution A is 1:3.

[0010] In some embodiments, the lead-containing compound includes lead iodide and lead bromide in a mass ratio of 1:2.

[0011] In some embodiments, the methylamine solution comprises methylamine iodide and methylamine chloride in a mass ratio of 1:1.

[0012] In some embodiments, the dispersion promoter includes butoxymethyl acrylamide and N-methyl-2-acrylamide in a mass ratio of 1:3.

[0013] In some embodiments, the enhancer includes hexamethylphosphoramide and 2-ethyl-5-methylthiophene in a mass ratio of 1:5.

[0014] In some embodiments, the toughening agent includes decanethiol functionalized silver nanoparticles and amino acid bonded silver nanoparticles in a mass ratio of 4:1.

[0015] According to an embodiment of the second aspect of the present application, a luminous anchor mesh material suitable for stress is proposed, which is obtained by the preparation method described in any of the above embodiments.

[0016] In some embodiments, the luminescent anchor mesh material emits yellow light with a wavelength of 570 nm under stress.

[0017] In the present application, holmium and dysprosium modified methylamine lead iodine bromine nanoparticles with stress luminescence characteristics are first prepared, and the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, polyimide matrix, dispersion promoter, reinforcing agent, and toughening agent are mixed and melt-spun and woven at 120-140°C to obtain a stress luminescent anchor net material suitable for lane deformation monitoring. The non-centrosymmetric crystal structure of the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles generates a piezoelectric potential when stimulated by force, thereby tilting the valence band and conduction band, reducing the trap depth, and making it easier for electrons to be unbound. The unbound electrons and holes undergo non-radiative transition recombination, and the energy of the non-radiative transition is transferred to holmium and dysprosium, so that they are excited and then emit yellow light of about 570nm. According to the intensity of the anchor net luminescence, the stress applied by the lane to the anchor net can be quantitatively judged. In addition, there is a difference in Young's modulus between holmium and dysprosium modified methylamine lead iodine bromine nanoparticles and the polyimide matrix. Holmium and dysprosium modified methylamine lead iodine bromine nanoparticles will cause the propagation cracks in the polyimide matrix to deflect, extend the crack propagation path, and improve the toughness of the anchor mesh material.

[0018] At the same time, in the anchor net material, the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles have a larger surface area than micron-sized particles at the same volume due to their small size, resulting in more active groups on their surface. These active groups can interact with molecules in the surrounding environment, showing high surface activity, and the interface strength between the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles and the polyimide matrix is ​​increased, thereby improving the strength of the anchor net material. The polar ions chloride ions and iodine ions on the surface of the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles and the amide groups in the polyimide matrix have intermolecular hydrogen bonding, which increases the cohesive energy in the polyimide matrix and improves the strength and toughness of the anchor net material.

[0019] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0021] Figure 1 It is a flow chart of the preparation method of the stress luminescent anchor mesh material proposed in one embodiment of the present application. DETAILED DESCRIPTION

[0022] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be construed as limiting the present application. On the contrary, the present application includes all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.

[0023] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0024] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0025] To achieve the above-mentioned purpose, according to the embodiment of the first aspect of the present application, a preparation method suitable for stress luminescent anchor mesh material is proposed. Figure 1 , including the following steps:

[0026] S1: dissolving a soluble salt containing holmium and dysprosium in a mixed solution A consisting of 2-acetylbenzofuran and 1-(1-benzofuran-2-yl)ethyl](methyl)amine, and then adding a lead-containing compound to the mixed solution to obtain a solution B; adding a methylamine solution dropwise to the solution B under stirring and ultrasonic conditions to obtain holmium and dysprosium modified methylamine lead iodine bromine nanoparticles;

[0027] S2: By weight, 10-15 parts of holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, 100 parts of polyimide matrix, 1-2 parts of dispersion promoter, 1-5 parts of reinforcing agent and 1-3 parts of toughening agent are stirred and mixed, and melt-spun and woven at 120-140° C. to obtain an anchor mesh material.

[0028] The soluble salts of holmium and dysprosium in S1 are dissolved in a mixed solution A consisting of 2-acetylbenzofuran and 1-(1-benzofuran-2-yl)ethyl](methyl)amine, and then a lead-containing compound is added to the mixed solution, and the mixture is stirred and dissolved evenly to obtain a solution B. While the solution B is stirred and ultrasonicated, a methylamine solution is added dropwise thereto, and the solution is filtered to obtain holmium and dysprosium modified methylamine lead iodine bromide (Ho / Dy-CH3NH3PbBrI2) nanoparticles, which have stress luminescence properties.

[0029] In the process of preparing holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, the soluble salts of holmium and dysprosium are 3-5 parts by mass; the soluble salts of holmium and dysprosium include holmium chloride, holmium iodide, dysprosium iodide and dysprosium chloride in a mass ratio of 1:1:3:1. In some embodiments, the mass fractions of holmium and dysprosium soluble salts are 3 parts, 4 parts or 5 parts, etc., wherein the mass fractions of holmium and dysprosium soluble salts are small, such as less than 3 parts, then the luminescence intensity of holmium and dysprosium modified methylamine lead iodine bromine nanoparticles is low and difficult to be detected. If the mass fractions of holmium and dysprosium soluble salts are large, such as more than 5 parts, the overall mechanical strength of the luminescent anchor mesh material is affected.

[0030] In the process of preparing holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, the mixed solution A is 20 parts by mass; wherein the mixed solution A includes 2-acetylbenzofuran and 1-(1-benzofuran-2-yl)ethyl](methyl)amine in a mass ratio of 1:3. If the mass fraction of the mixed solution A is small, such as less than 20 parts, the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles are poorly modified, and the stress luminescence intensity is not high. If the mass fraction of the mixed solution A is large, such as more than 20 parts, there will be a large number of residual unreacted small molecules, which will affect the overall mechanical strength and durability of the luminescent anchor mesh material.

[0031] Among them, in the process of preparing holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, the lead compound is 5-9 parts by mass; wherein the lead compound includes lead iodide and lead bromide in a mass ratio of 1:2. In some embodiments, the mass fraction of the lead compound is 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, etc., wherein the mass fraction of the lead compound is less, such as less than 5 parts, then the stress luminescence intensity is low and difficult to detect. If the mass fraction of the lead compound is large, such as greater than 9 parts, there will be more small molecules remaining, which affects the mechanical tensile strength of the luminous anchor material.

[0032] Wherein, in the process of preparing holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, the methylamine solution is 10-15 parts by mass; wherein the methylamine solution comprises methylamine iodide and methylamine chloride in a mass ratio of 1:1. In some embodiments, the mass fraction of the methylamine solution is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, etc., wherein the mass fraction of the methylamine solution is less, such as less than 10 parts, then the hydrogen bond strength in the system is low, and the overall mechanical strength of the anchor net is low. If the mass fraction of the methylamine solution is larger, such as greater than 15 parts, there will be a large number of residual small molecules, which will affect the tensile strength of the luminescent anchor net material.

[0033] Among them, in S2, by weight, 10-15 parts of holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, 100 parts of polyimide matrix, 1-2 parts of dispersion promoter, 1-5 parts of reinforcing agent, and 1-3 parts of toughening agent are stirred and mixed and melt-spun and woven at 120-140°C to obtain the anchor net material.

[0034] In the preparation process of the stress luminescent anchor net material, the mass fraction of the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles is 10-15 parts. In some embodiments, the mass fraction of the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, etc., wherein the mass fraction of the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles is small, such as less than 10 parts, then the luminescence intensity of the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles is low and difficult to be detected. If the mass fraction of the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles is large, such as more than 15 parts, the overall mechanical strength of the luminescent anchor net material is affected.

[0035] In the process of preparing the stress luminous anchor mesh material, the mass fraction of the polyimide matrix is ​​100 parts. In some embodiments, if the mass fraction of the polyimide matrix is ​​less, such as less than 100 parts, the tensile strength of the luminous anchor mesh material is insufficient. If the mass fraction of the polyimide matrix is ​​larger, such as greater than 100 parts, the stress luminous intensity of the luminous anchor mesh material is lower.

[0036] In the preparation process of the stress luminescent anchor mesh material, the mass fraction of the dispersion promoter is 1-2 parts, wherein the dispersion promoter includes butoxymethyl acrylamide and N-methyl-2-acrylamide in a mass ratio of 1:3. In some embodiments, the mass fraction of the dispersion promoter is 1 or 2 parts, etc., wherein the mass fraction of the dispersion promoter is less, such as less than 1 part, the dispersion is poor, agglomeration and phase separation are prone to occur, and the overall tensile strength is reduced. If the mass fraction of the dispersion promoter is large, such as greater than 2 parts, the tensile strength of the luminescent anchor mesh material is reduced.

[0037] In the preparation process of the stress luminous anchor net material, the mass fraction of the enhancer is 1-5 parts, wherein the enhancer includes hexamethylphosphoramide and 2-ethyl-5-methylthiophene in a mass ratio of 1:5. In some embodiments, the mass fraction of the enhancer is 1 part, 2 parts, 3 parts, 4 parts or 5 parts, etc., wherein the mass fraction of the enhancer is less, such as less than 1 part, the enhancement effect is not good, and the tensile strength of the luminous anchor net material is insufficient. If the mass fraction of the enhancer is larger, such as greater than 5 parts, the rigidity of the luminous anchor net material is higher and the flexibility is reduced.

[0038] In the preparation process of the stress luminescent anchor mesh material, the mass fraction of the toughening agent is 1-3 parts, wherein the toughening agent includes decanethiol functionalized silver nanoparticles and amino acid bonded silver nanoparticles in a mass ratio of 4:1. In some embodiments, the mass fraction of the toughening agent is 1 part, 2 parts or 3 parts, etc., wherein the mass fraction of the toughening agent is less, such as less than 1 part, then the toughening effect of the luminescent anchor mesh material is insufficient and the toughness is poor. If the mass fraction of the toughening agent is larger, such as greater than 3 parts, then the overall tensile strength and stiffness of the luminescent anchor mesh material are reduced.

[0039] According to an embodiment of the second aspect of the present application, a luminous anchor mesh material suitable for stress is proposed, which is prepared by a method in any of the above embodiments.

[0040] In some embodiments, the luminescent anchor mesh material emits yellow light with a wavelength of 570 nm under stress.

[0041] To facilitate further understanding of the present application, the scheme of the present application is further described below in conjunction with the embodiments. Those skilled in the art will understand that the description in the present application is only part of the examples, and any other suitable specific examples are within the scope of the present application.

[0042] Example 1

[0043] The present embodiment provides a luminous anchor mesh material suitable for stress, and its preparation method and specific operating parameters are as follows: 5 parts of holmium chloride, holmium iodide, dysprosium iodide, and dysprosium chloride are dissolved in 20 parts of a mixed solution of 2-acetylbenzofuran and 1-(1-benzofuran-2-yl)ethyl](methyl)amine, and then 8 parts of lead iodide and lead bromide are added to the mixed solution, and the mixture is stirred and dissolved evenly. While stirring and ultrasonicating the solution system, 14 parts of methylamine iodide and methylamine chloride are added dropwise thereto, and the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles are obtained by filtering.

[0044] By weight, 15 parts of holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, 100 parts of polyimide matrix, 1 part of dispersion promoter, 5 parts of reinforcing agent and 2 parts of toughening agent were stirred and mixed and melt-spun and woven at 120° C. to obtain an anchor mesh material.

[0045] Example 2

[0046] This embodiment is different from Embodiment 1 in the following aspects: in parts by mass, 10 parts of holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, 100 parts of polyimide matrix, 1 part of dispersion promoter, 2 parts of reinforcing agent and 3 parts of toughening agent are stirred and mixed and melt-spun and woven at 1140° C. to obtain an anchor mesh material.

[0047] Example 3

[0048] This embodiment is different from Embodiment 1 in the following aspects: in terms of mass fractions, 12 parts of holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, 100 parts of polyimide matrix, 2 parts of dispersion promoter, 1 part of reinforcing agent and 2 parts of toughening agent are stirred and mixed and melt-spun and woven at 130°C to obtain an anchor mesh material.

[0049] Example 4

[0050] This embodiment is different from Embodiment 1 in the following aspects: by weight, 11 parts of holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, 100 parts of polyimide matrix, 2 parts of dispersion promoter, 3 parts of reinforcing agent and 3 parts of toughening agent are stirred and mixed and melt-spun and woven at 140° C. to obtain an anchor mesh material.

[0051] Example 5

[0052] This embodiment is different from Embodiment 1 in the following aspects: in parts by mass, 14 parts of holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, 100 parts of polyimide matrix, 2 parts of dispersion promoter, 4 parts of reinforcing agent and 1 part of toughening agent are stirred and mixed and melt-spun and woven at 120° C. to obtain an anchor mesh material.

[0053] Experimental example

[0054] The luminous anchor mesh materials in each embodiment were tested after use, and the results are shown in Table 1.

[0055] Table 1 Performance results of anchor mesh materials in the embodiment

[0056]

[0057] It can be seen from the results in Table 1 that the luminous anchor net material provided in the present application has good luminous intensity and supporting effect.

[0058] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0059] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for preparing a stress luminous anchor net material, characterized in that: The following steps are involved: Dissolving a soluble salt containing holmium and dysprosium in a mixed solution A consisting of 2-acetylbenzofuran and 1-(1-benzofuran-2-yl)ethyl](methyl)amine, and then adding a lead-containing compound to the mixed solution to obtain a solution B; dropping a methylamine solution into the solution B under stirring and ultrasonic conditions to obtain holmium and dysprosium modified methylamine lead iodine bromine nanoparticles; By weight, 10-15 parts of the holmium and dysprosium modified methylamine lead iodine bromine nanoparticles, 100 parts of the polyimide matrix, 1-2 parts of the dispersion promoter, 1-5 parts of the reinforcing agent, and 1-3 parts of the toughening agent are stirred and mixed, and melt-spun and woven at 120-140° C. to obtain the anchor net material.

2. The preparation method according to claim 1, characterized in that: In terms of mass parts, the soluble salt containing holmium and dysprosium is 3-5 parts; the mixed solution A is 20 parts; the lead-containing compound is 5-9 parts; the methylamine solution is 10-15 parts; the soluble salt containing holmium and dysprosium includes holmium chloride, holmium iodide, dysprosium iodide and dysprosium chloride in a mass ratio of 1:1:3:

1.

3. The preparation method according to claim 1, characterized in that: The mixed solution A includes the 2-acetylbenzofuran and the 1-(1-benzofuran-2-yl)ethyl](methyl)amine in a mass ratio of 1:

3.

4. The preparation method according to claim 1, characterized in that: The lead-containing compound comprises lead iodide and lead bromide in a mass ratio of 1:

2.

5. The preparation method according to claim 1, characterized in that: The methylamine solution comprises methylamine iodide and methylamine chloride in a mass ratio of 1:

1.

6. The preparation method according to claim 1, characterized in that: The dispersion promoter includes butoxymethyl acrylamide and N-methyl-2-acrylamide in a mass ratio of 1:

3.

7. The preparation method according to claim 1, characterized in that: The enhancer comprises hexamethylphosphoramide and 2-ethyl-5-methylthiophene in a mass ratio of 1:

5.

8. The preparation method according to claim 1, characterized in that: The toughening agent comprises decanethiol functionalized silver nanoparticles and amino acid bonded silver nanoparticles in a mass ratio of 4:

1.

9. A luminous anchor net material suitable for stress, characterized in that: The compound is obtained by the preparation method described in any one of claims 1 to 8.

10. The luminous anchor mesh material according to claim 9, characterized in that: The luminous anchor mesh material emits yellow light with a wavelength of 570nm under stress.